Examen especial a los ingresos y gastos del gobierno autónomo descentralizado parroquial rural sumaco, cantón quijos, provincia de napo, en el periodo 2014 - Cajas Perez, Doris Mariela (2016)
It was developed with the firm intention of contributing to the procedures of special review and internal evaluation in this entity, in order to correct the accounting and financial procedures in the prior, concurrent and subsequent control of its operations for the period under this investigation. Special examinations in the financial field are of fundamental importance because it allows to establish the degree to which the institutions and bodies and their servants have properly fulfilled the duties and powers assigned to them, whether its functions have been implemented in an efficient and effective manner also because it allows to establish whether the objectives and institutional goals have been achieved and finally if the financial information generated is accurate and reliable. Different expectations were achieved in this study was required the application of techniques Special Examination that allowed to know the weaknesses and strengths that exist within the Gobierno Parroquial Sumaco, performing the respective narratives certificates for the Control System implemented in the institution, the same shall be communicated to the President and other members of the Vestry on the management of the components discussed in the Special Examination by a final report the results obtained during the course of the audit, so that by following the recommendations issued will contribute to efficient and effective management is detailed Income and expenses of the organization.